THE INFLUENCE OF COMPANY CHARCTERISTICS, GOOD CORPORATE GOVERNANCE, REPUTATION AND SHAREHOLDER PRESSURE ON ENVIRONMENTAL DISCLOSURE - Putri, Sucinda; Kurniawati Kurniawati (Dinasti International Journal of Management Science, 2022)
Environmental disclosure is a tool for the company to show its responsibilities to the environment. This study aims to investigate the influence of company characteristics, good corporate governance, reputation, and stakeholder pressure on environmental disclosure. This study uses purposive sampling technique and resulted a final sample of 53 (fifty three) manufacturing companies listed on IDX during 2017-2019. The analytic technique used in this study is multiple linear regression analysis. The result of this study shows that independent commissioners as part of good corporate governance mechanism, reputation and shareholders pressure have significant effect on environmental disclosure. Meanwhile, sales growth, profitability and environmental pressure have not significant effect on environmental disclosure. The conclusion of this study shows companies should consider any information needed by stakeholders, including environmental disclosure. For regulators, the results of this study can be a consideration to collaborate with parties that can increase awareness of the importance of environmental, such as independent commissioners and majority shareholders